Household survey data on income, food security and dietary behaviour among women and children from urban and per urban regions of Nairobi metropolitan - Nyakundi, Fridah Nyabate; Lung'aho, Mercy G.; Chege, Christine G. Kiria; Ndung'u, John; Nungo, Rhoda; Karanja, David (Alliance of Bioversity International and CIAT / Kenya Agricultural & Livestock Research Organization, 2020)
This data was collected in the context of a Cultivate Africa's Future (CultiAF) project on pre-cooked beans led by the Kenya Agricultural and Livestock Research Organization (KALRO) and Uganda's National Research Organization (NARO). A cross-sectional household survey that was carried out to assess key access constraints to nutritious foods among urban and peri-urban consumers. Participants included households with at least one child aged 6-59 months. Urban consumers were sampled from three sub-counties in Nairobi County: Kibera, Dandora, and Imara Daima. Peri-urban consumers were sampled from Athi River sub-county in Machakos County, and Juja sub-county in Kiambu County. (2020-07-01)